Literasi Digital Dalam Menunjang Pengelolaan Keuangan Organisasi : AI Sebagai Asisten Digital : Pengabdian - Nuryani, Anum; Hidayat, Arif; Muhammad Lutfi, Asep (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The objective of this Community Service activity is to provide training in financial management using AI. This program is designed to help administrators understand proper financial recording techniques. The community service team collaborated with ORKI to carry out community service activities related to education on the use of Artificial Intelligence in financial management. The stages of this activity included identification, compilation of a pocket book, education through lectures, evaluation, and publication. The target audience for this community service activity was all ORKI members, not just its structural members. The activity was carried out offline at the base camp in South Tangerang on October 11-12, 2025, and was attended by 37 participants, including the ORKI South Tangerang administrators. The results of the activity, which were evaluated using an online multiple-choice test, showed that the level of understanding of the participants in the education provided was >75% of participants obtained a Good score (80-100).